Theory and practice of academic education in architecture and urban design: from bilateral cooperation to international projects - Cherkes, Bohdan; Linda, Svitlana; Kolomyeytsev, Anton (Видавництво Львівської політехніки, 2016)
This article presents analyses of thoughts and ideas expressed at the international symposium, which was dedicated to the 20th anniversary of cooperation between the Institute of Architecture of Lviv Polytechnic National University and the Faculty of Architecture and Planning of Vienna University of Technology.The results of cooperation and perspectives of its further development are considered in the context of presented ideas. Проаналізовано думки та ідеї, задекларовані на міжнародному симпозіуму, приуроченому 20-й річниці кооперації між Інститутом архітектури Національного університету “Львівська політехніка” та архітектурним факультетом Віденського технічного університету. Результати кооперації та перспективи її подальшого розвитку розглянуто у контексті поданих ідей.
Теорія та практика академічної освіти в архітектурі та містобудуванні: від двосторонньої кооперації до міжнародних проектів
Keywords: academic cooperation; architecture; urbanism; EU; Institute of Architecture of Lviv Polytechnic National University; Faculty of Architecture and Planning of Vienna University of Technology; академічна кооперація; архітектура; містобудування; ЄС; Інститут архітектури Національного університету “Львівська політехніка”; факультет архітектури та планування Віденського технічного університету